Estudo das variantes RHD em pacientes portadores da Doença Falciforme do Estado do Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
Introduction:Studies have demonstrated the presence of RHD variants in sickle cell patients, resulting in subsequent alloimuzation, because of the Rh protein having structural function in membranes of these cells, other factors derived from these polymorphisms may impact on the length of life of the erythrocyte. The frequency of RHD variants is not yet known in sickle cell patients in the state of Amazonas and if there the possibility of association between these variants and blood transfusion in these individuals. Objective: Our aim was to investigate the variants of RHD in sickle cell patients in the State of Amazonas Materials and methods: We performed phenotyping of samples from patients with sickle cell disease by hemagglutination tube method using the reagent anti-D IgG clone MS201 and anti-D IgM clone MS26. The Multiplex PCR genotyping method was performed for characterization RHD regions of the Intron 4 and exon 7 and the exons 3, 4, 5, 6, 7 and 9 for the characterization of vari ant RhD.The statistical method of Chi Square was used for analysis of retrospective information on the number of transfusions and the presence of RhD variants. Results: We analyzed 128 samples, of which 45 (35.15%) showed discrepant results in serology for detec tion of RhD antigen and 12 (9.37%) patients with RhD variants. However 03 of these showed no discrepancies in RhD serology. While 33 discrepant samples in serological test s were not characterized as RhD variant. Among the variants, 07 (58.33%) were characterized as DVa, where such individuals were concentrated up to 32 RhD positive red cells without developing anti-RhD, 01 (8.33%) DFR presenting the frequency of transfusion 18 concentrated RhD positive red cells also without the presence of anti-RhD and 04 (33.33%) samples classified as indeterminate, and 2 of these patients had alloimmunization by anti-RhD. Discussion: Our results demonstrate that not all discrepancies in serological tests is indicative of variant RhD and that these results can be found 4 crosses for two reagents. The DVa variant was more frequent in our sickle cell patients and this is not associated with anti-RhD alloimmunization by patients with multiple transfusions in RhD positive red blood cells, thus contrasting with the frequency of DIIIa found in these type of patients studied in other regions of Brazil and associated with increased risk of alloimmunization. Conclusion: In conclusion, we observed that molecular biology tests are needed to detect the RHD gene. The variations DVa patients may not develop anti-D when transfused with RhD-positive erythrocytes. We found indications that the presence of RhD variants are not associated with the need for transfusions in patients with sickle cell disease.
Keywords: Doença Falciforme; Polimorfismos; Hemocentro do Amazonas; Sorologia; CIENCIAS DA SAUDE: MEDICINA